2015
DOI: 10.3897/bdj.3.e4187
|View full text |Cite
|
Sign up to set email alerts
|

Fauna Europaea: Diptera – Brachycera

Abstract: Fauna Europaea provides a public web-service with an index of scientific names (including important synonyms) of all extant multicellular European terrestrial and freshwater animals and their geographical distribution at the level of countries and major islands (east of the Urals and excluding the Caucasus region). The Fauna Europaea project comprises about 230,000 taxonomic names, including 130,000 accepted species and 14,000 accepted subspecies, which is much more than the originally projected number of 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…We found a small but significant positive correlation between distance matrices of community composition and elevation. Previous studies of invertebrate fauna in the Alps have found changes in community composition at higher elevations, for example, reports of an increase in the proportion of Diptera relative to other orders (Pape et al., ), and a decrease in the species richness of wild bees (Hoiss, Krauss, Potts, Roberts, & Steffan‐Dewenter, ). Studies to date have been based on populations of free‐living invertebrates, whereas here we examined the contents of a carnivorous plant.…”
Section: Discussionmentioning
confidence: 99%
“…We found a small but significant positive correlation between distance matrices of community composition and elevation. Previous studies of invertebrate fauna in the Alps have found changes in community composition at higher elevations, for example, reports of an increase in the proportion of Diptera relative to other orders (Pape et al., ), and a decrease in the species richness of wild bees (Hoiss, Krauss, Potts, Roberts, & Steffan‐Dewenter, ). Studies to date have been based on populations of free‐living invertebrates, whereas here we examined the contents of a carnivorous plant.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 132 species of Sarcophagidae were listed from Turkey (Hayat et al 2008; Kara and Pape 2002; Koçak 2014; Koçak and Kemal 2009, 2012, 2013, 2015; Pape et al 2015; Pekbey 2011; Pekbey and Hayat 2011; Whitmore, 2011; Whitmore et al 2013). Our findings increase this number to 154.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason some of the records presented in this paper are not actually new even though they do not appear on the Fauna Europaea site. Moreover, the Fauna Europaea website did not separate Serbia and Montenegro (Pape et al 2015). …”
Section: Discussionmentioning
confidence: 99%